Discovery of a novel unsymmetrical structural class of HCV NS5A inhibitors with low picomolar antiviral activity. Issue 5 (1st March 2020) - Nakamura, Hiroshi; Akagi, Yusuke; Terui, Takashi; Fujioka, Shingo; Komoda, Yasumasa; Kinoshita, Wataru; Maeda, Kimiya; Ukaji, Yutaka; Inaba, Takashi
Graphical abstract: Abstract: A novel unsymmetrical structural class of HCV NS5A inhibitors showing picomolar range antiviral activity has been identified. An unsymmetrical lead compound 2, generated from a substructure of a known symmetrical inhibitor 1, was optimized by extension of its substituents to interact with the hitherto unexplored site of the target protein. This approach afforded novel highly potent unsymmetrical inhibitor 20, which not only equally inhibited HCV genotypes1a, 1b, and 2a with EC50 values in the picomolar range, but also inhibited the 1a Q30K mutant induced by a launched symmetrical inhibitor daclatasvir with an EC50 in the low nanomolar range.